"Exposure to the insecticides permethrin and malathion induces leukemia and lymphoma-associated gene aberrations in vitro". (October 2017) - Navarrete-Meneses, M.P.; Salas-Labadía, C.; Sanabrais-Jiménez, M.; Santana-Hernández, J.; Serrano-Cuevas, A.; Juárez-Velázquez, R.; Olaya-Vargas, A.; Pérez-Vera, P.
Abstract: Epidemiological studies have associated the exposure to permethrin and malathion with increased risk of leukemia and lymphoma. The aim of this study was to evaluate whether in vitro exposure to permethrin and malathion induces aberrations in genes involved in the etiology of these hematological malignancies. Genetic abnormalities in the IGH, KMT2A ( MLL), ETV6 and RUNX1 genes, and aneuploidy induced by the in vitro exposure to permethrin and malathion (200 μM, 24 h), were analyzed by FISH in peripheral blood mononuclear cells (PBMCs). The gene fusions IGH-BCL2, KMT2A-AFF1 and ETV6-RUNX1 were further analyzed with nested RT-PCR in PBMCs, and in K562 cells exposed to acute and chronic treatments (0.1 μM, 24 h or every third day for two weeks) of insecticides. FISH analysis revealed that permethrin induces aneuploidy and structural alterations in IGH and KMT2A genes, and malathion induces breaks in KMT2A . RT-PCR detected ETV6-RUNX1 fusion in PBMCs acutely exposed to permethrin. Permethrin also induced ETV6-RUNX1 and IGH-BCL2 fusions in K562 cells, and malathion induced KMT2A-AFF1 and ETV6-RUNX1 fusions. Overall, we identified that both insecticides induce breaks and fusions in the studied genes, and permethrin induces aneuploidy. This study presents evidence of damage in cancer genes caused by these insecticides. Highlights: Permethrin induces breaks in KMT2A and IGH genes in peripheral blood mononuclear cells (PBMCs) exposed in vitro . Permethrin induces aneuploidy in PBMCs exposed in vitro . Malathion induces KMT2A breaks in PBMCs exposed in vitro . Permethrin and malathion induced oncogenic fusions in PBMCs and K562 cells.